Utilização do DNA Barcoding como ferramenta no estudo do ictioplâncton e na avaliação do estabelecimento de espécies não-nativas - Cavaretto, Rafael Cezar (2019)
The identification of the megadiverse Neotropical fish fauna is a major challenge, especially in the early stages of development, when the few diagnostic characters can still be shared between species. In order to overcome the limitations of traditional taxonomy, molecular techniques, such as DNA Barcoding, have been successfully used to identify fish in their various life stages, due to their ability to discriminate species, even when closely allied. Thus, the present study aimed to evaluate the joint use of the traditional taxonomy, based on morphometric and meristic characters, and DNA Barcoding in the identification of the ichthyoplankton community in three tributaries of the Porto Primavera Reservoir, in the Upper Paraná River basin. This molecular technique was also used to evaluate the establishment (reproduction and recruitment) of non-native species in this basin, particularly Leporinus tigrinus Borodin, 1929. The results of this study reveal that the use of DNA Barcoding can significantly increase the taxonomic resolution achieved by classical identification. However, when used preliminarily, traditional taxonomic identification can optimize time, reduce costs and guide the sampling of the material to be routed to molecular identification. The DNA Barcoding also contributed to classify L. tigrinus as a non-native species and to confirm its establishment in the Upper Paraná River basin. This species presents a model of introduction and dispersion different from most alien species established in this basin.